#TITLE_ALTERNATIVE# - PRANITA ANDRIYATI (NIM : 20510010); Pembimbing : Prof. Dr Buchari, KORY
The increasing need of the gold metal, encourage large-scale exploration for gold metal to povide high number of requests. Commencement of the mineral exploitation of low-grade gold will certainly involve a variety of research or exploratory analyzes involving various chemical components in the low-grade gold mineral. The analysis must also involve the determination of follow-up metals such as iron (Fe) and silver (Ag), because the content of follow-up metals will also affect the gold content. The iron will affect the content of gold, because gold is usually attached to the iron mineral compounds such as magnetite and pyrite. Analysis of metal content in low grade auriferous ores require certain reference materials that have a similar profile to the material to be analyzed. Price of the reference material, known as the Reference Material is not cheap though can be used repeatedly. This is the challenge to make a reference for levels of certain metals in low grade gold ore that can be used in the laboratory itself to determine content of iron (Fe) and measurements repeatability. Research will prepare a reference material for analyzing content of iron (Fe) that present in low levels of gold mineral (Au content below 1ppm), method that use the is in-house atomic absorption spectrometry (AAS). Low grade gold ores used as raw material in advance Reference Material polished by grinding and homogenized with a 200 mesh sieve size automatically, the initial composition test performed by method of XRF and XRD. Material homogeneity test was conducted by atomic absorption spectroscopy (AAS) in ore raw materials that have been refined based on the content of Fe and Na, determination of homogeneity of materials carried by the F test (ANOVA) at 99.5% confidence level to conclude that the material was homogeneous with each calculated value of Fcounting smaller than F table. In this study also studied how the effects of low grade gold mineral preconcentration based on liquid density using bromoform (rho = 2.89 g.mL-1). Preconcentration effects were observed mainly on the content of silica compounds that have lowmass (rho = 1.65 g.mL-1) and the iron (Fe) content in the thigh-mass compounds such as pyrite (rho = 4.9 g.mL -1) and magnetite (rho = 5.21 g.mL-1) are present in low grade gold mineral. Because of the large density of bromoform, major components of rocks such as silicates and other light minerals will float. The principle of the extraction process with bromoform is the density difference. Expected with this physical separation will experience the process of concentration of gold in the sinking phase. Content of silica compounds obtained in the initial sample is 86.77%, while after preconsentration the floating fraction was 39.87% and 49.02% fraction was drowned. Levels of iron and silica compounds are analyzed in the initial sample and the fraction that is formed after the preconcentration indicate the presence of additive properties. Then do the testing measurements repeatability to determine the confidence interval at 95% and 99% confidence at the beginning of the gold ore mineral spectrometric atomic absorption method (AAS), the confidence interval obtained in 95% of the 56.556 ppm + 0.442 ppm and in 99% is 56.556 ppm + 0.635 ppm